PENGEMBANGAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN PPKN DENGAN PENDEKATAN PROBLEM BASED LEARNING DI KELAS VI SEKOLAH DASAR - Devita Eka Rahmadani; Linda Zakiah; Adi Putra (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This development research aims to develop and test the feasibility of a product in the form of audio-visual media in Civics learning with a problem-based learning approach in class VI of elementary schools. Audio visual media that is created combines audio, text, images and animation into an animated video that can make it easier for students to understand the material. This research was conducted at SDN Kelapa Dua Wetan 02 with class VI students as research subjects. The research method used is R&D (Research and Development) with the Thiagarajan 4D development model. This development model consists of 4 stages, namely: Difine, Design, and Disseminate. Data collection techniques used are observation, interviews, and questionnaires. Based on the results of the study, it can be concluded that the development of audio-visual media in Civics learning with a problem-based learning approach in class VI of elementary school is valid and very feasible for use in learning activities. This can be seen from the acquisition of scores by material experts, linguists and media experts, namely an average score of 93.33% in the Very Valid category and one to one trial assessment results of 96.88%, small group trials 95.33 % and 94.05% field test with Very Valid category. The implication of this research is that it is proven that the use of audio-visual media can make students understand the material presented because it is conveyed concretely so that students can achieve learning objectives in a fun way..